DEVELOPMENT OF A MICROELECTRONIC CODE TRANSMITTER FOR AUTOMATION AND TELEMECHANICS SYSTEMS IN RAILWAY TRANSPORT AND MODELING OF ITS PRINCIPLES OF OPERATION (American Journal of Interdisciplinary Research and Development, 2022)
Nowadays, microprocessor and microelectronic elements are widely used in the development of systems and devices for railway automation and telemechanics. The use of microelectronics and microprocessor technology in systems and devices of railway automation and telemechanics not only expands the working functions of its elements in comparison with electromagnetic relay systems, but also improves the correct organization and operation technology of these systems and devices.